A Community Education-Based Waste Management System: Addressing Urbanization and the Impacts of Climate Change in Makassar - Muh. - Syukri; Mulkhairi ikram; andi akbar; Muhammad Isnan Rasyidi; Wina Ayu Giswanti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze a waste management system based on public education in addressing urbanization and the impacts of climate change in Makassar City. Increasing urbanization has led to an increase in the volume of household waste and increasing pressure on the urban environment, particularly in Manggala District, the location of the Tamangapa Final Disposal Site (TPA). This study used a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. Research informants consisted of the Manggala District Government, waste bank managers, PT Pegadaian, and the community. The results showed that waste management based on public education is carried out through a collaborative governance approach between the government, the private sector, and the community through the Waste Bank and "The Gade Clean and Gold" programs. The education system is carried out through socialization of waste sorting, the formation of environmentally friendly behavior, and the provision of economic incentives in the form of gold savings. The study found that public education is an important instrument in increasing citizen participation in waste management while strengthening urban environmental resilience to the impacts of urbanization and climate change. However, low public awareness, limited facilities, and uneven distribution of environmental education remain major obstacles in program implementation. This study confirms that waste management based on public education can be a model for sustainable urban environmental development.